Interactive Immunomodulation in the Mediterranean Mussel Mytilus galloprovincialis Under Thermal Stress and Cadmium Exposure - Nardi, Alessandro; Benedetti, Maura; Gorbi, Stefania; Regoli, Francesco (Frontiers in Marine Science, 2021)
Marine bivalves are frequently exposed to multiple co-occurring challenges such as temperature extremes and anthropogenic pollution. These stressors can elicit negative effects on several biological pathways, including antioxidant and neuroendocrine-immune (NEI) systems, leading to immune disorders and altered immunocytes functionality. Since interactive mechanisms of action and resulting outcomes are still scarcely explored, we examined the single and combined effects of increased temperature (+5°C) and cadmium (20 μg/L) in the Mediterranean mussel Mytilus galloprovincialis. Analyzed parameters included cholinergic system in gills and hemolymph (acetylcholinesterase activity, AChE), total oxyradical scavenging capacity in gills and key functional processes in hemocytes, including lysosomal membrane stability, hemocytes subpopulations ratio, phagocytosis capacity, and onset of genotoxic damage. Results highlighted interactive inhibition of AChE activity along to a concomitant increased total oxyradical scavenging capacity, confirming neuroendocrine-immune system (NEI) disturbance and oxidative pressure. In hemocytes, lysosomal membrane stability and granulocytes:hyalinocytes ratio revealed additive effects of stressors, while a consistent reduction of phagocytosis was caused by temperature stress, with a slightly antagonistic effect of cadmium. Pearson’s correlation statistics provided either positive or negative relationships between investigated parameters and stressors, allowing to hypothesize putative mechanism of immune system functional alterations. The overall results suggest that the occurrence of short-term events of increased temperature and concomitant metal exposure could elicit interactive and negative effects on immune system efficiency of marine organisms.